SOSIALISASI PEMBELAJARAN AIR CONDITIONING MAINTENANCE BAGI SISWA SMKN 5 SURABAYA - Priyo Agus Setyawan; Emie Santoso; Aminatus Sa’diyah; Eky Novianarenti; Mey Rohmadhani; Imah Luluk Kusminah; Invinandri Joko Ahmad; Mayriza Mubarokah Tambas (Jurnal Cakrawala Maritim, 2023)
Skills related to safety and maintenance engineering are needed in the industrial world. Challenges in the future require all academics, both high school and vocational levels, to continue honing their soft skills to answer the issue of the industrial revolution 4.0. The idea of ??soft skills training activities related to safety and maintenance for State Vocational High School students in Surabaya was formed. With all the support of the various PPNS academics from lecturers, students, and students together to collaborate to contribute to these activities. The aim is none other than to provide students with knowledge and skills to be ready to face the challenges of the world of work in the future. This service activity is carried out using training and mentoring methods for students of SMKN 5 Surabaya. Training is conducted online and offline (Blended method or hybrid). Some joined online via video conference (Vicon). It is hoped that with this activity, students will have basic skills in the field of safety, including: basic K3 competencies, then skills in the field of air conditioning maintenance are that students are able to carry out periodic maintenance of AC components both from a mechanical and electrical perspective, and are also able to perform maintenance according to schedule by considering the slogan plan, do, check, action.